A Proposta Curricular de Ciências no município de São Paulo (2019): aproximações e distanciamentos com a concepção educacional freireana - Hippler, Elis Laura Pinto Rieger (Universidade Federal de São Carlos, 2020)
In the field of education, in studies on the curriculum, there are different trends and philosophical positions, some of which are considered critical and others not. However, broader ways of conceiving the curriculum started to be built from authors who were based on the critical theoretical production from the philosophical materialism-historical-dialectic position. Among these authors are Paulo Freire, who contributed significantly to the understanding of the curriculum from an emancipatory and democratic educational perspective. In view of Freire's influence on curriculum policies, for his literary works and for his role as Secretary of Education in the city of São Paulo, categories that are critically understood in this educational concept, were disseminated and transformed in polysemic terms. From this, the fact that the Science curriculum of Nature of the city of São Paulo, published in 2019, contemplate the categories dialogue, concrete reality, and subject, present in the critical Freire perspective, made this document object of study in this research. Thus, the general objective of this work is to understand the conceptions of these concepts proposed in the Natural Sciences curriculum (2019), in the city of São Paulo, they are related, or not, with curricular proposal implemented in Freire's management in the SME-SP (1989). For this, a qualitative analysis of the documents was carried out, which had as a philosophical basis and as a theoretical-methodological basis the materialist-historical-dialectic. Thus, documents were selected that would be relevant to the research, selecting, in this way, the formation notebook created in the management of Paulo Freire, in the SME-SP (1989-1992), published in 1992, as well as the “Vision of the area” notebook of Sciences. In addition to the document prepared by SME-SP, in 2019, entitled “Curriculum of the City of Natural Sciences” (second edition). Based on the results obtained, it was considered that, in general, the document analyzed appeared, at times, to be close to critical curricular aspects, such as the Freirean one, in what concerns the conceptions of dialogue, concrete reality, and subject. However, the document showed to be more related to an uncritical and non-Freirean educational and curricular conception than to a critical and Freirean one, as they are closer to the principles from the positivist philosophical position that can be found in the technicist curriculum perspective.
The Science Curriculum Proposal in the city of São Paulo (2019): approximations and distances with the Freirean educational conception
Keywords: Currículo de Ciências; Currículo Crítico; Diálogo; Freire; Realidade Concreta; Sujeito; Science Curriculum; Critical Curriculum; Freire; Dialogue; Concrete Reality; Subject; CIENCIAS HUMANAS::EDUCACAO